Transport buyers choice of transport service – A literature review of empirical results. (June 2017) - Flodén, Jonas; Bärthel, Fredrik; Sorkina, Edith
Graphical abstract: Highlights: Price is most important when choosing transport services. Quality related factors are also of high importance. Environmental impact is given very low importance. There is great consistency among the studies about the most important factors. Both peer-reviewed and non-peer reviewed studies come to the same main conclusions.